INCIDENCE OF HBV, HCV AND HIV AMONG THE BLOODDONORS IN A TERTIARY CARE CENTRE, KOLKATA - DR. ASHIS KUMAR SAHA, M.D.(CAL), D.T.M & H (CAL), FICP, FACP; DR. PAYODHI DHAR, M.B.B.S (CAL) (International Journal of Pharma and Bio Sciences, 2016)
Blood transfusion a life saving procedure in many critical cases may transmit hepatitis B, C, HIV viruses. According to WHO, these diseases should be screened in the donated blood before keeping it ready for transfusion. So, it is necessary to know the prevalence of HBV, HCV and HIV infections in the blood donors. Obviously, our aim in this present study is to detect the prevalence of seropositivity of HBV, HCV and HIV in the donors in K P C Medical College and Hospitals, Kolkata. In this retrospective study, serological tests of HBV, HCV and HIV viruses were done in total 7044 blood donors. Number of seropositive donors were collected and tabulated according to age groups, analyzed in Excel and were compared with the data of different studies worldwide. Ratio of male to female donors was 5.55:1. Most of the donors were from 21 to 40 years. Among 7044 donors, the overall prevalence of HBV, HCV and HIV seropositivity were 1.19%, 0.2% and 0.11% respectively. Males were significantly involved, but sex wise (males: 5969, females: 1075), no significant involvement was seen in male. In our study, there was a low prevalence of HBV, HCV and HIV seropositivity which may be due to non-use of updated method of laboratory testing for donor screening, lack of public awareness to donate blood, lack of proper educational programs and vigilance error. So, continuous public awareness program for above diseases, avoidance of professional donors, updated method of laboratory testing can reduce actual incidence of seropositivity in donors.